Diagnostic accuracy of ultrasound in the detection of malignant breast lesions / Aimuni Shafiqah Azme and Mohd Hafizi Mahmud - Azme, Aimuni Shafiqah; Mahmud, Mohd Hafizi (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Some small lesions could be missing with mammography, particularly in dense breasts. Therefore, ultrasound is an alternative non-ionizing tool for breast imaging. This study aims to determine the diagnostic accuracy of ultrasound in detecting malignant breast lesions and the association of malignancy status with demographic and clinical factors. A total of 70 medical reports of patients who underwent breast ultrasonography between January and December 2023 were retrospectively reviewed. The lesion malignancy was validated using the biopsy as a reference standard. Diagnostic accuracy test was performed using Bayesian Theorem. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of ultrasound in detecting benign and malignant breast lesions were 97.6%, 27.6%, 65.6%, and 88.9% respectively with overall diagnostic accuracy of 68.6%. The malignancy of lesions was significantly associated with age (p = 0.015), family history (p = 0.004) and fertility status (p = 0.004). The approximately 70% diagnostic accuracy of ultrasound suggests that this non-ionizing imaging modality could not be used independently for a definitive diagnosis of breast malignancy but needs a comprehensive integrated approach with mammography and other diagnostic imaging tools.